Investigation of slug mitigation: self-lifting approach in a deepwater oil field - Adefemi, Israel; Kara, Fuat; Okereke, N. U. (Society for Underwater Technology, 2017)
Slug flow is a flow assurance issue that staggers production and, in some cases, 'kills the flow' of the well. Severe slugging, a type of slugging which usually occurs at the base of the riser column, causes large amplitudes in the fluctuation of pressure within the riser column and consequently damages equipment placed topside. An adaptation of a novel concept to slug mitigation: the self-lifting model, is presented. This model presents variations to the internal diameter of the self-lift bypass to produce effective mitigation to severe slugging.
Keywords: OLGA; Riser base pressure; Self-lift; Severe slugging; Slug